Corn Tiller Yield Contributions are Dependent on Environment: A 17 Site-Year Kansas Study - R. L. Veenstra; D. Berning; P. Carter; S. Wallace; M. Legleiter; L. Currie; C. D. Messina; P. V. Vara Prasad; T. J. Hefley; L. A. Haag; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2022)
Historic breeding efforts in corn (Zea maysL.) have resulted in uniform, single-stalked phenotypes with limited potential for environmental plasticity. Therefore, plant density is a critical yield component for corn, as corn is unable to successfully compensate for a deficit of plants. Other grass crop species can overcome plant density deficits via vegetative branching (tillering), but this trait is historically undesirable in corn. Improving corn flexibility across plant densities has potential benefits, particularly considering diverse yield environments and seasonal weather uncertainties due to climate change. The present study evaluated tiller presence with two hybrids in a range of plant densities across the state of Kansas to identify yield impacts and potential usefulness of this plasticity trait in corn. Tiller presence was identified as neutral or additive to final yields, but fine-tuning plant density was confirmed as key to maximizing grain yields. Tillers have potential to stabilize yields across plant densities in productive environments. This capability may offer a source of production stability for growers when deficits develop in plant density after planting.
Keywords: corn; tiller; yield; plant density; crop plasticity